MICROBIOLOGICAL QUALITY AND STORABILITY OF LANDRACE PORK GIVEN KPLA (Chicken Farm Waste Protein Concentrate) - D.M., Sitio; Ariana, I N. T.; Sriyani, N. L. P. (Jurnal Peternakan Tropika; Vol 12 No 2 (2024): Vol. 12 No. 2 Tahun 2024; March - April, 2024)
This study aimed to determine the microbiological quality and storability of landrace pork on the provision of protein concentrate based on broiler farm waste (KPLA) through pig ration feed. This study used a completely randomized design consisting of three treatments and five replications. The treatment consisted of P0 (ration with 24% CP.152 + 0% KPLA), P1 (ration with 12% CP.152 + 12% KPLA), P2 (ration with 0% CP.152 + 24% KPLA). The observed variable is Total Plate Count (TPC), Coliform , Escherichia coli , and the storability of meat. Data on total bacterial values ??were analyzed using variance. The results showed that landrace pig meat given KPLA produced the highest average value in treatment P1 with a TPC of 7.3 x 10 4 cfu/g, Coliform of 3.6 x 10 4 cfu/g, and Escheria coli of 0.6 x 10 1 cfu/g. The conclusion of this study was that meat from crossbreed landrace pigs fed KPLA had total microbial/TPC and Escherichia coli which increases and was inside  the SNI safe limit. Total Coliform increased but was outside the SNI safe limit.The shelf life of meat in this study was 3 hours, with the highest microbial total in treatment P2 of 2,3 x 10 9 cfu/g at 6 hours of storage.